Resting state and personality component (BIS/BAS) predict the brain activity (EEG and fNIRS measure) in response to emotional cues - Balconi, Michela (Brain Behav, 2017)
INTRODUCTION: The present study explored the role of resting state and personality component (BIS/BAS measure) on prefrontal cortical responsiveness to emotional cues. Indeed, we supposed that lateralized resting activity (right vs. left) and approach (BAS) versus avoidance (BIS) attitude may explain the successive emotional processing within the prefrontal cortex (PFC) based on the stimulus valence (positive and negative emotional cues). METHODS: Hemodynamic (functional near‐infrared spectroscopy, fNIRS) and electroencephalographic (EEG) measures were considered. The resting and experimental brain activity were registered when subjects (N = 21) viewed emotional positive versus negative stimuli (International Affective Picture System, IAPS). LIR (eeg) and LIR (nirs) (lateralized Index Response) during resting state, and LI (eeg) and LI (nirs) during emotional processing were acquired. RESULTS: A set of regression analyses was applied to the multiple measures. The predictive effect of resting activity and approach/avoidance dichotomy were elucidated. Indeed, more left/right resting activity (for both LIR (eeg) and LIR (nirs)) predicted the successive more brain left/right response (LI (eeg) and LI (nirs)) to emotional cues. Second, significant effects were revealed as a function of valence (increased right response to negative stimuli; increased left response to positive stimuli) during emotion processing. Third, higher BAS values explained an increased left cortical activity in resting state and in experimental condition for positive cues. In contrast, higher BIS values marked an increased right activity in resting state and in experimental condition in response to negative cues. CONCLUSION: The significance of trait component for both resting and emotional cue processing was discussed at light of the present results.